Corporate social responsibility performance among listed non-financial firms in Nigeria - Echobu, John; Echobu, Faith Oluwatosin (Journal of Asian Business Strategy, 2023)
The extent of involvement in Corporate Social Responsibility (CSR) by companies in Nigeria is required in order to know the level of acceptance and actual performance of CSR demands on the companies. This descriptive research design study was carried out using data from the annual reports (2010-2019) of listed non-financial companies in Nigeria. Social and environmental disclosures based on the Global Reporting Initiative framework (GRI-4) were used. Social disclosure is measured as an index score generated from the score of 1 or 0 for disclosures or otherwise on community, donation, employee, health and safety, and customer/complaints. Environmental disclosure represents an index score generated from the score of 1 or 0 for disclosures or otherwise on material, energy, water, biodiversity, emission/greenhouse gas, waste management, product services, and compliance with laws. The companies are involved in activities that contribute more to social sustainability than environmental sustainability, accounting for an aggregate average performance score of 0.71 (71%) and 0.03 (3%) for social and environmental responsibility respectively. The firms contributed significantly to social responsibility and very little with no significant performance in environmental responsibility. The very low environmental responsibility performance among these firms is worrisome and calls for investigation into the existing national environmental regulatory frameworks.